102k views
1 vote
What is (1-7x)(1+9x)

2 Answers

5 votes

Answer:

1+2x-63x^2

Explanation:

factor 1(1+9x)=1+9X

-7x(1+9x)=-7x-63x^2

add 1+9x-7x-63x2

User Umair Shah
by
5.0k points
4 votes

ANSWER


(1-7x)(1+9x) =- 63 {x}^(2) + 2x + 1

EXPLANATION

The given product is (1-7x)(1+9x).

Expand using the distributive property.


(1-7x)(1+9x) = 1(1 + 9x) - 7x(1 + 9x)


(1-7x)(1+9x) = 1 + 9x - 7x - 63 {x}^(2)

Simplify to obtain:


(1-7x)(1+9x) = 1 + 2x - 63 {x}^(2)

You can rewrite in standard form to get,


(1-7x)(1+9x) =- 63 {x}^(2) + 2x + 1

User Panya
by
5.2k points